Optimised photodynamic diagnosis for transurethral resection of the bladder (TURB) in German clinical practice: results of the noninterventional study OPTIC III - Bach, Thorsten (World journal of urology, 2017)
PurposeWhite light cystoscopy (WLC) is the standard procedure for visualising non-muscle invasive bladder cancer (NMIBC). However, WLC can fail to detect all cancerous lesions, and outcomes with transurethral resection of the bladder differ between institutions, controlled trials, and possibly between trials and routine application. This noninterventional study assessed the benefit of hexaminolevulinate blue light cystoscopy (HALC; Hexvix, Ipsen Pharma GmbH, Germany) plus WLC versus WLC alone in routine use.MethodsFrom May 2013 to April 2014, 403 patients with suspected NMIBC were screened from 30 German centres to perform an unprecedented detailed assessment of the additional detection of cancer lesions with HALC versus WLC alone.ResultsAmong the histological results for 929 biopsy samples, 94.3 % were obtained from suspected cancerous lesions under either WLC or HALC: 59.5 % were carcinoma tissue and 40.5 % were non-cancerous tissue. Of all cancer lesions, 62.2 % were staged as Ta, 20.1 % as T1, 9.3 % as T2, 7.3 % as carcinoma in situ (CIS), and 1.2 % were unknown. Additional cancer lesions (+6.8 %) and CIS lesions (+25 %, p < 0.0001) were detected by HALC plus WLC versus WLC alone. In 10.0 % of patients, ≥1 additional positive lesion was detected with HALC, and 2.2 % of NMIBC patients would have been missed with WLC alone. No adverse events were observed.ConclusionsThe results of this study demonstrate that HALC significantly improves the detection of NMIBC versus WLC alone in routine clinical practice in Germany. While this benefit is statistically significant across all types of NMIBC, it seems most relevant in CIS.